2007
DOI: 10.1371/journal.pone.0000898
|View full text |Cite
|
Sign up to set email alerts
|

Evidence Based Selection of Housekeeping Genes

Abstract: For accurate and reliable gene expression analysis, normalization of gene expression data against housekeeping genes (reference or internal control genes) is required. It is known that commonly used housekeeping genes (e.g. ACTB, GAPDH, HPRT1, and B2M) vary considerably under different experimental conditions and therefore their use for normalization is limited. We performed a meta-analysis of 13,629 human gene array samples in order to identify the most stable expressed genes. Here we show novel candidate hou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
622
2
3

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 666 publications
(652 citation statements)
references
References 15 publications
25
622
2
3
Order By: Relevance
“…Bactericidal/permeability-increasing (BPI) fold-containing family A1 4 (BPIFA1; also called SPLUNC1) is a glycoprotein that is highly expressed in the 5 respiratory epithelium and submucosal glands of the upper airways in mice and 6 humans [2][3][4][5][6][7][8][9] . The mouse and human BPIFA1 sequences are homologous 8, 10, 11 .…”
mentioning
confidence: 99%
“…Bactericidal/permeability-increasing (BPI) fold-containing family A1 4 (BPIFA1; also called SPLUNC1) is a glycoprotein that is highly expressed in the 5 respiratory epithelium and submucosal glands of the upper airways in mice and 6 humans [2][3][4][5][6][7][8][9] . The mouse and human BPIFA1 sequences are homologous 8, 10, 11 .…”
mentioning
confidence: 99%
“…Due to the fact that ribosomal proteins represent adequate housekeeping genes in quantitative real-time PCR (qrtPCR) in general (de Jonge et al 2007), a partial sequence of the ribosomal protein S13 gene (rps13) was used as reference gene in this study. The efficiency of the PCR reactions was calculated from the slope of the standard curve, which was derived from a dilution series (1:2, 1:20, 1:200 and 1:2,000).…”
Section: Experimental Designmentioning
confidence: 99%
“…Therefore, during the detection of target gene expression, a gene with a stable expression is required as a reference. Recent studies have revealed defects in all commonly used reference genes, which often vary greatly in expression quantity in various types of cells and tissues, stages of cell amplification and organ development and in vitro culture and experimental conditions (9,10,(20)(21)(22). To the best of our knowledge, there have been no systematic comparisons performed concerning the stability of commonly-used reference genes in CCA tissues and cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…grade and stage of tumors, and as previous studies indicate, the expression of a reference gene is not directly associated with the grade and stage of malignant tumors (21); the selected samples were all characterized as malignant tissue samples by the pathology department of the China-Japan Union Hospital of Jilin University, and the pathology observed in the samples indicated the most common pathological type of CCA, adenocarcinoma; the QBC939 cell line was also used as it is a commonly used human CCA cell line; the stability evaluation on reference genes for the selected histological samples and cell lines of human CCA was implemented to make the experimental results more comprehensive, compared with previous studies (9,10,21,22) where the stability evaluation on reference genes was restricted on ceratin tissues or cell lines; and the stability of 12 common reference genes was compared.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation